Variação interanual (2000-2005) da comunidade fitoplanctônica em um lago de inundação isolado do Parque Estadual do rio Ivinhema (MS). - Scomparin, Vânia Mara Bovo (2007)
The aim of this research was to analyze the interannual variation of the phytoplanktonic community composition, density (Utermöhl method), biomass (estimated by the biovolume), size structure (GALD) and species richness in relation with environmental factors, in an isolated floodplain lake (Ventura lagoon) located at Ivinheima River State Park (Mato Grosso, Brazil). The phytoplankton samplings were realized quarterly, at subsurface of pelagic zone of the lagoon, between February of 2000 and march of 2006, except in 2003, when were done just two samplings, and in 2005, when was done an additional sampling in February. There were identified 132 taxa, with Chlorophyceae as the group presenting more species. The species richness was higher in June of 2005, the same year that this lagoon was flooded. The highest values of phytoplanktonic density were observed in November of 2001 (3068 ind.mL- 1), March of 2003 (2897 ind.mL-1) and June of 2005 (3171 ind.mL-1), with dominance of Cyanobacteria, Bacillariophyceae and Cryptophyceae nanoplanktonic species (<20 μm). The highest biovolume values occur in August (36,28 mm3.L-1) and November of 2002 (31,38 mm3.L-1) and in June of 2005 (28,23 mm3.L-1). High-size Cyanobacteria species presented the highest contribution for the phytoplanktonic biovolume, in which Anabaena planctonica and Radiocystis fernandoi were dominant. The seasonal variation of the phytoplanktonic biomass in Ventura lagoon suggests a deterministic influence of the hydro-sedimentological regime of Paraná and Ivinhema Rivers upon this environment. In general, during the periods that this influence was high, low biovolume values were verified, with Bacillariophyceae and Cryptophyceae as the groups with most contribution, whereas Cyanobacteria was the dominant group during the low-water periods. Probably, La Niña and El Niño phenomenon contributed to the interannual variation of the phytoplanktonic community. In 2000 and 2001, under the influence of La Niña phenomenon, Cyanobacteria was massively dominant. In 2002, 2003, 2004 and 2005, during the influence of El Niño phenomenon, besides Cyanobacteria, Bacillariophyceae and Cryptophyceae were also dominant.